การปรับปรุงวิธีการตอกเสาเข็มสำหรับเสาเข็มคอนกรีตสั้น - ศิวะพล กอวัฒนะ (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
Short concrete piles are widely used for a foundation bearing low weight structure such as fence and one story building. From field investigation, it is found that, in many cases, current practices in Thailand for short concrete pile driving do not comply with engineering standards. The objective of this research is to present an improvement of a pile driving method for short concrete piles. The study covers literature review of related engineering theory comparing with data collected from pile drive contractors. In Thailand, the methods of short concrete pile driving are in three practices which are (a) pile driving using manpower, (b) pile driving using an excavation machine, and (c) pile driving using a small piling rig. This study reveals that incorrect procedures are found in short concrete pile driving, for instance, neglect in examining of vertical alignment, incorrect engineering practices of machine operations, and unsafe driving procedures. This research introduces an assisting tool to improve a short concrete pile priving process. In time, cost, and quality aspects, the proposed tool is developed to support a pile driving method using an excavation machine. Design concepts of an assisting tool are generated from the truss of piling rig and the telescopic prop. With these concepts, it is found that (a) the vertical alignment of driven piles is better, (b) construction cost is low, and (c) small numbers of workers are required. In terms of productivity, the method of using the proposed tool provides better results than those of using manpower and piling rigs.